Срок для Бешеного: [роман] / Виктор Доценко - Доценко Виктор Николаевич (Вагриус, 1997)
Экземпляры: Ф4 (20181121) / Инвентарный номер: 56733 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: Д 71 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6